Current knowledge about FLT3 gene mutations, exploring the isoforms, and protein importance in AML - Macečková, Diana; Vaňková, Lenka; Holubová, Monika; Jindra, Pavel; Klieber, Robin; Jandová, Eliška; Pitule, Pavel (Molecular biology reports, 2024)
Acute myeloid leukaemia (AML) is a complex haematological malignancy characterised by diverse genetic alterations leading to abnormal proliferation of myeloid precursor cells. One of the most significant genetic alterations in AML involves mutations in the FLT3 gene, which plays a critical role in haematopoiesis and haematopoietic homeostasis. This review explores the current understanding of FLT3 gene mutations and isoforms and the importance of the FLT3 protein in AML. FLT3 mutations, including internal tandem duplications (FLT3-ITD) and point mutations in the tyrosine kinase domain (FLT3-TKD), occur in 25-30% in AML and are associated with poor prognosis. FLT3-ITD mutations lead to constitutive activation of the FLT3 signalling pathway, promoting cell survival and proliferation. FLT3-TKD mutations affect the tyrosine kinase domain and affect AML prognosis in various ways. Furthermore, FLT3 isoforms, including shorter variants, contribute to the complexity of FLT3 biology. Additionally, nonpathological polymorphisms in FLT3 are being explored for their potential impact on AML prognosis and treatment response. This review also discusses the development of molecular treatments targeting FLT3, including first-generation and next-generation tyrosine kinase inhibitors, highlighting the challenges of resistance that often arise during therapy. The final chapter describes FLT3 protein domain rearrangements and their relevance to AML pathogenesis.
Keywords: Cell Survival; Leukemia, Myeloid, Acute; fms-Like Tyrosine Kinase 3; protein - isoformy; mutace; Protein Isoforms; FLT3; tyrosinkinasa 3 podobná fms; Humans; Mutation; Acute myeloid leukaemia; Protein-Tyrosine Kinases; lidé; tyrosinkinasy; Gene isoforms; Mutations; akutní myeloidní leukemie; viabilita buněk